Urban-rural Gaps in Early Initiation of Breastfeeding (IEBF) Practices: Evidence from Thailand - Intarti, Wiwit Desi; Siregar, Renince; Siantar, Rupdi Lumban; Rostianingsih, Dewi; Suyitno, Suyitno; Maretalinia, Maretalinia (Jurnal Kesehatan Masyarakat, 2024)
The evidence that several factors can play a role as risk factor on initiation of breastfeeding. This study aimed to examine the risk factor of initiation of early breastfeeding in Thailand that differentiate by place of residence. This study used secondary data from MICS (Multiple Indicators Cluster Survey) of Thailand in 2022. Total sample lived in Urban area is 1226 and those lived in Rural area is 1,430. The analysis of this study has differentiated to urban area. The statistical test used is STATA. The prevalence of EIBF in urban. The findings of both place of residence revealed that delivery by caesarean section as risk factor in the urban and rural area with AOR 2.5 and 1.93 times respectively. Others risk factors in urban are formally married and in rural are the risk factors are delivery with practical nurse, and low birth weight of baby. The factors that supporting EIBF implementation are wealth index with AOR 0.48 and 1.46 respectively. Government and stockholders can focus to support the financial issue in the households to decrease the probability of not EIBF. Future study can include more variables in households and community levels and add the qualitative approach.